2010
DOI: 10.1007/s10151-010-0633-9
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic impact of anastomotic leakage after low anterior resection for rectal cancer

Abstract: Anastomotic leakage is a severe complication after rectal cancer surgery. This review article is focused in the incidence, the risk factors, the management and the oncologic impact of anastomotic leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Increasing evidence exists on the association between improved postoperative courses and the possibility of receiving adjuvant therapy appropriately, given that deferred receipt of adjuvant chemotherapy has been shown in multiple studies to negatively affect survival . Indeed, surgical complications, particularly anastomotic leakage, have proven to be associated with a poor survival after the curative resection of colorectal cancer, a higher LR rate of rectal malignancies and lengthened intervals between surgery and adjuvant treatments and postoperative hospital stay, morbidity and anastomotic complications were not significantly different between laparoscopic and robot‐assisted surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence exists on the association between improved postoperative courses and the possibility of receiving adjuvant therapy appropriately, given that deferred receipt of adjuvant chemotherapy has been shown in multiple studies to negatively affect survival . Indeed, surgical complications, particularly anastomotic leakage, have proven to be associated with a poor survival after the curative resection of colorectal cancer, a higher LR rate of rectal malignancies and lengthened intervals between surgery and adjuvant treatments and postoperative hospital stay, morbidity and anastomotic complications were not significantly different between laparoscopic and robot‐assisted surgery.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of functional outcomes, laparoscopic procedure has been found to be, at the least, not inferior to open surgery, with several reports suggesting it has even better results in preserving postoperative genitourinary function and especially sexual activity . Nevertheless, a deterioration in urinary and especially sexual function still represents an established risk after rectal surgery with mesorectal excision .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Postoperative complications after major surgery have been shown to increase length of stay, cost, and early mortality. 7-10 Potential explanations for a relationship between infectious complications and oncologic outcomes include (1) proliferation of proinflammatory cytokines and mediators, both locally and systemically, 7,11,12 (2) the association of SSIs with increased stage, 13 (3) delays in the initiation of adjuvant treatments as a result of postcomplication care, 9 (4) escape of intraluminal neoplastic cells in the case of anastomotic leak, 9,14,15 and/or (5) poor surgical technique, which may increase both the incidence of cancer recurrence and infectious complications. [4][5][6] Specifically in CRC, there have been mixed data regarding the association of deep SSIs/anastomotic leaks with long-term survival, with multiple studies demonstrating conflicting results.…”
mentioning
confidence: 99%
“…Several studies have demonstrated an increase in local recurrence rate and a decreased overall survival, while other studies have failed to demonstrate this connection. A recent study showed that AL, which required reoperation, was associated with a significantly higher local recurrence and lower overall survival rate [1].In most cases, the clinical presentation of AL is insidious with vague and uncharacteristic abdominal symptoms, which may be masked by the use of epidural analgesia. Some cases may present with extraintestinal manifestations such as atrial fibrillation or mental confusion.…”
mentioning
confidence: 99%
“…Several studies have demonstrated an increase in local recurrence rate and a decreased overall survival, while other studies have failed to demonstrate this connection. A recent study showed that AL, which required reoperation, was associated with a significantly higher local recurrence and lower overall survival rate [1].…”
mentioning
confidence: 99%